A Population-based Investigation of Circadian Rhythm of Intraocular Pressure in Habitual Position Among Healthy Subjects: The Handan Eye Study. Issue 7 (July 2016) - Wang, Ning Li; Hao, Jie; Zhen, Yi; Liu, John H.K.; Li, Si Zhen; Wang, Hao; Chen, Hui; Peng, Xiao Xia; Han, Wei; Fan, Su Jie; Weinreb, Robert N.
Abstract : Purpose: (1) To investigate the reference value of peak-trough difference in circadian rhythm of intraocular pressure (IOP) in habitual position and (2) to compare the IOP parameters among 3 age groups. Materials and Methods: Habitual IOP of healthy subjects sampled from the population in the Handan Eye Study was measured every 2 hours in the seated position during light-wake period (7:30 AM, 9:30 AM, 11:30 AM, 1:30 PM, 3:30 PM, 5:30 PM, 7:30 PM, 9:30 PM) and in the supine position during dark-sleep period (11:30 PM, 1:30 AM, 3:30 AM, 5:30 AM). Blood pressure and heart rate were obtained subsequently at each IOP measurement. Results: Two hundred six healthy subjects were included in the final analyses (n=20, 30 to 39 y old; n=95, 40 to 49 y old; n=91, 50 to 59 y old). For peak-trough difference (7.2±2.3 mm Hg; 6.8 to 7.5 mm Hg, 95% confidence interval) in habitual position, the reference value was described as median 7.0 mm Hg, 25th percentile 5.5 mm Hg, and 95th percentile 11.5 mm Hg. No significant differences in peak-trough difference, acrophase (cosine-fit analysis derived peak timing) and amplitude (half distance between the cosine-fit maximum and minimum) were found among the 3 age groups. In the cosine model, the nocturnal acrophase (3:49±0.53 AM; 3:42 to 3:55 AM, 95% confidence interval) was detected for the entire group. Furthermore, 106 subjects (52%) had a nocturnal peak pattern, 36 subjects (17%) had a diurnal peak pattern, and 64 subjects (31%) had no evident pattern. Conclusions: In habitual position, 75% of healthy subjects from a population-based investigation had IOP variation >5.5 mm Hg and 95% subjects had <11.5 mm Hg variation. Aging may not influence the circadian habitual IOP rhythm.